In Vitro and In Vivo Anticancer Effects of Sterol Fraction from Red Algae Porphyra dentata. (26th August 2013) - Kazłowska, Katarzyna; Lin, Hong-Ting Victor; Chang, Shun-Hsien; Tsai, Guo-Jane
Abstract : Porphyra dentata, an edible red macroalgae, is used as a folk medicine in Asia. This study evaluated in vitro and in vivo the protective effect of a sterol fraction from P. dentata against breast cancer linked to tumor-induced myeloid derived-suppressor cells (MDSCs). A sterol fraction containing cholesterol, β -sitosterol, and campesterol was prepared by solvent fractionation of methanol extract of P. dentata    in silica gel column chromatography. This sterol fraction in vitro significantly inhibited cell growth and induced apoptosis in 4T1 cancer cells. Intraperitoneal injection of this sterol fraction at 10 and 25 mg/kg body weight into 4T1 cell-implanted tumor BALB/c mice significantly inhibited the growth of tumor nodules and increased the survival rate of mice. This sterol fraction significantly decreased the reactive oxygen species (ROS) and arginase activity of MDSCs in tumor-bearing mice. Therefore, the sterol fraction from P. dentata showed potential for protecting an organism from 4T1 cell-based tumor genesis.